The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12877-016-0401-4
|View full text |Cite
|
Sign up to set email alerts
|

Making the Most of Mealtimes (M3): protocol of a multi-centre cross-sectional study of food intake and its determinants in older adults living in long term care homes

Abstract: BackgroundOlder adults living in long term care (LTC) homes are nutritionally vulnerable, often consuming insufficient energy, macro- and micronutrients to sustain their health and function. Multiple factors are proposed to influence food intake, yet our understanding of these diverse factors and their interactions are limited. The purpose of this paper is to fully describe the protocol used to examine determinants of food and fluid intake among older adults participating in the Making the Most of Mealtimes (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 78 publications
3
73
0
Order By: Relevance
“…This study was part of a national cross‐sectional study, Making the Most of Mealtimes (M3), examining the factors influencing food and fluid intake in long‐term care . Four provinces, Alberta, Manitoba, Ontario and New Brunswick, each contributed 8 long‐term care homes to the project.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a national cross‐sectional study, Making the Most of Mealtimes (M3), examining the factors influencing food and fluid intake in long‐term care . Four provinces, Alberta, Manitoba, Ontario and New Brunswick, each contributed 8 long‐term care homes to the project.…”
Section: Methodsmentioning
confidence: 99%
“…Ethics approval was received from the University of Alberta (Pro00050002), University of Manitoba (J2014:139), University of Waterloo (ORE 20056) and Université de Moncton (1415‐022). A detailed protocol of the full M3 study has been published elsewhere and summarised below and focused on the data used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Study sample and design M3 was a cross-sectional multi-site Canadian study; details on the primary research questions and comprehensive data collection can be found in the protocol [28]. This was a secondary study, based solely on the planned menus of the homes.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient analysis was completed using ESHA Food Processor software (Version 10.14.1) using the Canadian Nutrient File [29], where appropriate, for foods that varied in fortification practices with the United States Department of Agriculture Nutrient File [30]. A code-book was created per province to promote consistency in database choices for selected menu items [28]. A random check of menu items was completed by the first author to ensure accuracy in use of the Canadian Nutrient File for key foods among provinces; this check was especially focused for provinces that showed significant nutrient differences from others to confirm that differences in nutrient content were not a result of a provincial research assistant bias in recipe/food item selection from the database.…”
Section: Nutrient Analysismentioning
confidence: 99%
See 1 more Smart Citation